One-third of patients fail to return to work 1 year after surgery for colorectal cancer - Bhalla, Ashish; Williams, John P.; Hurst, N.G.; Speake, W.J.; Tierney, G.M.; Tou, S.; Lund, Jonathan N. (Springer Verlag, 2014)
Background